Second Place: Marine Life - Rodríguez, Federico J (NSUWorks, 2023)
"Galápagos Sea Lion (Zalophus wollebaeki)" Galápagos sea lion sleeping in boulder surrounded by Sally Lightfoot crabs. Photo taken in North Seymour island - Galápagos, Ecuador. https://nsuworks.nova.edu/occ_shuttershark_2024/1136/thumbnail.jpg